Preparation method of positive electrode material for improving cycle performance of LMFP battery
The modified LMFP material, Kochen Black and Zr(SO4)2 were prepared by mixing and sintering the ball mill to prepare the modified LMFP material, which solved the problems of short cycle life and large particle size of the LMFP battery, and significantly improved the cycle performance and charge and discharge performance of the battery.
Patent Information
- Application Number
- CN202411825311.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-12
- Publication Date
- 2025-03-14
AI Technical Summary
The cycle life of LMFP batteries is short and the large particle size affects the charge and discharge performance.
By mixing the LMFP material, Kochen Black and Zr(SO4)2 ball mill and sintering under a nitrogen atmosphere, the modified LMFP material was prepared and mixed uniformly with the binder and the conductive agent to form a positive electrode material.
The conductivity of modified LMFP materials has been greatly improved, the dissolution of manganese elements has been inhibited, and the circulation performance and charge and discharge performance have been significantly improved.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of LMFP batteries, in particular to a method for preparing a positive electrode material for improving the cycle performance of a LMFP battery. Background Art
[0002] In recent years, customers have placed increasingly higher demands on battery performance. Charge and discharge performance under high voltage as well as cycle performance are also areas that many power battery manufacturers continue to develop.
[0003] Lithium iron phosphate (LFP) material has a limited voltage platform, but the introduction of manganese has increased the voltage platform of LFP from 3.4V to 4.1V of LMFP, which is a breakthrough in voltage platform. However, the dissolution of manganese will shorten the cycle life; at the same time, LMFP has a large particle size, and directly using it as a positive electrode active material will also affect the charge and discharge performance and cycle life.
[0004] In summary, it is of great significance to prepare a positive electrode material to improve the cycle performance of LMFP batteries. Summary of the invention
[0005] The object of the present invention is to provide a method for preparing a positive electrode material for improving the cycle performance of a LMFP battery, so as to solve the problems raised in the above background technology.
[0006] In order to solve the above technical problems, the present invention provides the following technical solutions: A method for preparing a positive electrode material for improving the cycle performance of a LMFP battery comprises the following steps: S1: LMFP material, Ketjen black and Zr(SO4)2 are mixed evenly by ball milling, and sintered in a nitrogen atmosphere to obtain an active material; S2: The active material, the binder, and the conductive agent are uniformly mixed to obtain a positive electrode slurry; the positive electrode slurry is coated on an aluminum foil, and dried to obtain a positive electrode material.
[0007] More optimally, the mass ratio of the LMFP material to Ketjen black is (150-155):1; the mass ratio of the LMFP material to Zr(SO4)2 is (200-205):1.
[0008] More optimally, the mass ratio of the modified LMFP material, the binder and the conductive agent is 96:2.5:1.5; the binder includes PVDF; and the conductive agent includes Super P.
[0009] The more optimized process conditions for the sintering treatment are: a heating rate of 45-50°C / min, an annealing rate of 20-25°C / min, a calcination temperature of 750-800°C, and a sintering time of 7-8 hours.
[0010] The optimal ball milling speed is 800 rpm / min and the ball milling time is 20 min.
[0011] More optimally, the LMFP material includes conventional LMFP material and composite LMFP material; the preparation method of the composite LMFP material is: lithium carbonate, manganese carbonate, iron phosphate, dopant, and ammonium dihydrogen phosphate are added to an ethanol aqueous solution and ball-milled for 7 to 9 hours, sucrose is added and ball-milled for 7 to 9 hours, and dried at 50 to 60° C. to obtain a precursor; in a nitrogen atmosphere, the precursor is calcined at 400 to 500° C. for 4 to 5 hours, and the temperature is raised to 650 to 700° C. and calcined for 10 to 12 hours to obtain a composite LMFP material.
[0012] More optimally, the molar ratio of the lithium carbonate, manganese carbonate, iron phosphate, dopant, diammonium phosphate, and sucrose is (1-1.2):(0.5-0.8):(0.2-0.24):(0.03-0.04):1:(0.05-0.07).
[0013] More optimally, the doping agents are zinc carbonate and magnesium carbonate in a molar ratio of (3-4):1; in the ethanol aqueous solution, the mass ratio of ethanol to deionized water is 1:(1-2).
[0014] Compared with the prior art, the beneficial effects achieved by the present invention are: The present invention prepares a modified LMFP material (lithium manganese iron phosphate), high-conductivity Ketjen black, and Zr(SO4)2 by ball milling, mixing, and calcining; Among them, the LMFP material (lithium manganese iron phosphate) has a too strong PO bond, resulting in low electronic conductivity; the highly conductive Ketjen black can coat the LMFP material, which can not only inhibit the dissolution of manganese elements, but also greatly increase the conductivity of the material, thereby improving the cycle performance of the battery; Zr(SO4)2 provided by calcination 4+ It can enhance the conductivity and stability of the electrode and improve the battery life; at the same time, the ball milling process can reduce the size of LMFP, which is more conducive to its transmission during the charging and discharging process at the battery end.
[0015] Since the lithium ion diffusion efficiency of the one-dimensional diffusion channel of lithium ions is low, the LMFP material (lithium manganese iron phosphate) is optimized by the method of bimetallic doping. In the scheme, zinc carbonate and yttrium carbonate are used as dopants to synergistically modify the LMFP material in situ to obtain a composite LMFP material.
[0016] The incorporation of zinc can optimize the crystal structure and reduce the volume change caused by the insertion and extraction of lithium ions, thereby reducing the stress and potential phase change of LMFP materials; zinc can reduce the dissolution of manganese and enhance the cycle stability of LMFP materials during the charge and discharge process; yttrium doping can reduce LiFe x Mn y PO4 and Fe x Mn y The strain between the PO4 phase interfaces can enhance the structural stability of the material during the charge and discharge cycle; and significantly reduce its potential polarization, promote the reduction kinetics of manganese ions, and effectively improve the diffusion coefficient of lithium ions at 4.1V. DETAILED DESCRIPTION
[0017] The following is a preferred implementation of the embodiment of the present invention. Obviously, the described embodiment is only a part of the embodiment of the present invention, not all of the embodiments. For ordinary technicians in this technical field, all other embodiments obtained by ordinary technicians in this field without creative work without departing from the principle of the embodiment of the present invention are within the scope of protection of the present invention.
[0018] The preparation method of conventional LMFP material is as follows: lithium carbonate, manganese carbonate, iron phosphate, and ammonium dihydrogen phosphate are added to an ethanol aqueous solution (the mass ratio of ethanol to deionized water is 1:1) and ball-milled for 7 hours, sucrose is added and ball-milled for 8 hours, and dried at 55°C to obtain a precursor; in a nitrogen atmosphere, the precursor is calcined at 500°C for 4 hours, and the temperature is increased to 700°C and calcined for 12 hours to obtain a composite LMFP material.
[0019] Example 1: A method for preparing a positive electrode material for improving the cycle performance of a LMFP battery; S1: conventional LMFP material, Ketjen black and Zr(SO4)2 were ball-milled at 800 rpm / min for 20 min, and sintered at 800°C for 8 h in a nitrogen atmosphere to obtain an active material; Among them, the mass ratio of conventional LMFP material to Ketjen black is 155:1, and the mass ratio of LMFP material to Zr(SO4)2 is 205:1; the heating rate of sintering is 50℃ / min, and the annealing rate of sintering is 25℃ / min; S2: The active material, binder (KF1100) and conductive agent (Super P) are uniformly mixed to obtain a positive electrode slurry; the positive electrode slurry is coated on a 12μm aluminum foil and dried at 120°C for 12 hours to obtain a positive electrode material; wherein the mass ratio of the active material, binder and conductive agent is 96:2.5:1.5.
[0020] Example 2 Based on Example 1, the mass ratio of LMFP material to Ketjen black is 145:1; S1: conventional LMFP material, Ketjen black and Zr(SO4)2 were ball-milled at 800 rpm / min for 20 min, and sintered at 800°C for 8 h in a nitrogen atmosphere to obtain an active material; Among them, the mass ratio of LMFP material to Ketjen black is 145:1, and the mass ratio of LMFP material to Zr(SO4)2 is 205:1; the heating rate of sintering is 50℃ / min, and the annealing rate of sintering is 25℃ / min; S2: The active material, binder (KF1100) and conductive agent (Super P) are uniformly mixed to obtain a positive electrode slurry; the positive electrode slurry is coated on a 12μm aluminum foil and dried at 120°C for 12 hours to obtain a positive electrode material; wherein the mass ratio of the active material, binder and conductive agent is 96:2.5:1.5.
[0021] Example 3 is based on Example 1: the mass ratio of LMFP material to Ketjen black is 150:1; S1: conventional LMFP material, Ketjen black and Zr(SO4)2 were ball-milled at 800 rpm / min for 20 min, and sintered at 800°C for 8 h in a nitrogen atmosphere to obtain an active material; Among them, the mass ratio of conventional LMFP material to Ketjen black is 150:1, and the mass ratio of LMFP material to Zr(SO4)2 is 205:1; the heating rate of sintering is 50℃ / min, and the annealing rate of sintering is 25℃ / min; S2: The active material, binder (KF1100) and conductive agent (Super P) are uniformly mixed to obtain a positive electrode slurry; the positive electrode slurry is coated on a 12μm aluminum foil and dried at 120°C for 12 hours to obtain a positive electrode material; wherein the mass ratio of the active material, binder and conductive agent is 96:2.5:1.5.
[0022] Example 4 is based on Example 1: the mass ratio of LMFP material to Ketjen black is 160:1; S1: conventional LMFP material, Ketjen black and Zr(SO4)2 were ball-milled at 800 rpm / min for 20 min, and sintered at 800°C for 8 h in a nitrogen atmosphere to obtain an active material; Among them, the mass ratio of conventional LMFP material to Ketjen black is 160:1, and the mass ratio of LMFP material to Zr(SO4)2 is 205:1; the heating rate of sintering is 50℃ / min, and the annealing rate of sintering is 25℃ / min; S2: The active material, binder (KF1100) and conductive agent (Super P) are uniformly mixed to obtain a positive electrode slurry; the positive electrode slurry is coated on a 12μm aluminum foil and dried at 120°C for 12 hours to obtain a positive electrode material; wherein the mass ratio of the active material, binder and conductive agent is 96:2.5:1.5.
[0023] Example 5 is based on Example 1: the mass ratio of LMFP material to Ketjen black is 165:1; S1: conventional LMFP material, Ketjen black and Zr(SO4)2 were ball-milled at 800 rpm / min for 20 min, and sintered at 800°C for 8 h in a nitrogen atmosphere to obtain an active material; Among them, the mass ratio of LMFP material to Ketjen black is 165:1, and the mass ratio of LMFP material to Zr(SO4)2 is 205:1; the heating rate of sintering is 50℃ / min, and the annealing rate of sintering is 25℃ / min; S2: The active material, binder (KF1100) and conductive agent (Super P) are uniformly mixed to obtain a positive electrode slurry; the positive electrode slurry is coated on a 12μm aluminum foil and dried at 120°C for 12 hours to obtain a positive electrode material; wherein the mass ratio of the active material, binder and conductive agent is 96:2.5:1.5.
[0024] Example 6 is based on Example 1: the mass ratio of LMFP material to Zr(SO4)2 is 195:1; S1: conventional LMFP material, Ketjen black and Zr(SO4)2 were ball-milled at 800 rpm / min for 20 min, and sintered at 800°C for 8 h in a nitrogen atmosphere to obtain an active material; Among them, the mass ratio of conventional LMFP material to Ketjen black is 155:1, and the mass ratio of LMFP material to Zr(SO4)2 is 195:1; the heating rate of sintering is 50℃ / min, and the annealing rate of sintering is 25℃ / min; S2: The active material, binder (KF1100) and conductive agent (Super P) are uniformly mixed to obtain a positive electrode slurry; the positive electrode slurry is coated on a 12μm aluminum foil and dried at 120°C for 12 hours to obtain a positive electrode material; wherein the mass ratio of the active material, binder and conductive agent is 96:2.5:1.5.
[0025] Example 7 is based on Example 1: the mass ratio of LMFP material to Zr(SO4)2 is 200:1; S1: conventional LMFP material, Ketjen black and Zr(SO4)2 were ball-milled at 800 rpm / min for 20 min, and sintered at 800°C for 8 h in a nitrogen atmosphere to obtain an active material; Among them, the mass ratio of conventional LMFP material to Ketjen black is 155:1, and the mass ratio of LMFP material to Zr(SO4)2 is 200:1; the heating rate of sintering is 50℃ / min, and the annealing rate of sintering is 25℃ / min; S2: The active material, binder (KF1100) and conductive agent (Super P) are uniformly mixed to obtain a positive electrode slurry; the positive electrode slurry is coated on a 12μm aluminum foil and dried at 120°C for 12 hours to obtain a positive electrode material; wherein the mass ratio of the active material, binder and conductive agent is 96:2.5:1.5.
[0026] Example 8 is based on Example 1: the mass ratio of LMFP material to Zr(SO4)2 is 210:1; S1: conventional LMFP material, Ketjen black and Zr(SO4)2 were ball-milled at 800 rpm / min for 20 min, and sintered at 800°C for 8 h in a nitrogen atmosphere to obtain an active material; Among them, the mass ratio of conventional LMFP material to Ketjen black is 155:1, and the mass ratio of LMFP material to Zr(SO4)2 is 210:1; the heating rate of sintering is 50℃ / min, and the annealing rate of sintering is 25℃ / min; S2: The active material, binder (KF1100) and conductive agent (Super P) are uniformly mixed to obtain a positive electrode slurry; the positive electrode slurry is coated on a 12μm aluminum foil and dried at 120°C for 12 hours to obtain a positive electrode material; wherein the mass ratio of the active material, binder and conductive agent is 96:2.5:1.5.
[0027] Example 9 is based on Example 1: the mass ratio of LMFP material to Zr(SO4)2 is 215:1; S1: conventional LMFP material, Ketjen black and Zr(SO4)2 were ball-milled at 800 rpm / min for 20 min, and sintered at 800°C for 8 h in a nitrogen atmosphere to obtain an active material; Among them, the mass ratio of conventional LMFP material to Ketjen black is 155:1, and the mass ratio of LMFP material to Zr(SO4)2 is 215:1; the heating rate of sintering is 50℃ / min, and the annealing rate of sintering is 25℃ / min; S2: The active material, binder (KF1100) and conductive agent (Super P) are uniformly mixed to obtain a positive electrode slurry; the positive electrode slurry is coated on a 12μm aluminum foil and dried at 120°C for 12 hours to obtain a positive electrode material; wherein the mass ratio of the active material, binder and conductive agent is 96:2.5:1.5.
[0028] Example 10 is based on Example 1, except that the LMFP material is replaced with a composite LMFP material; S1: (1) The preparation method of the composite LMFP material is as follows: lithium carbonate, manganese carbonate, iron phosphate, dopant, and ammonium dihydrogen phosphate are added to an ethanol aqueous solution (the mass ratio of ethanol to deionized water is 1:1) and ball-milled for 7 hours, sucrose is added and ball-milled for 8 hours, and dried at 55°C to obtain a precursor; in a nitrogen atmosphere, the precursor is calcined at 500°C for 4 hours, and the temperature is raised to 700°C and calcined for 12 hours to obtain a composite LMFP material; The molar ratio of lithium carbonate, manganese carbonate, iron phosphate, dopant, diammonium phosphate and sucrose is 1:0.8:0.2:0.03:1:0.05; the molar ratio of zinc carbonate to magnesium carbonate in the dopant is 3:1; (2) The composite LMFP material, Ketjen black and Zr(SO4)2 were ball-milled at a speed of 800 rpm / min for 20 min, and sintered at 800°C for 8 hours in a nitrogen atmosphere to obtain an active material; Among them, the mass ratio of the composite LMFP material to Ketjen black is 150:1, and the mass ratio of the LMFP material to Zr(SO4)2 is 200:1; the sintering heating rate is 50℃ / min, and the sintering annealing rate is 25℃ / min; S2: The active material, the binder (KF1100), and the conductive agent (Super P) are uniformly mixed to obtain a positive electrode slurry; the positive electrode slurry is coated on a 12 μm aluminum foil and dried at 120° C. for 12 hours to obtain a positive electrode material; Among them, the mass ratio of active material, binder and conductive agent is 96:2.5:1.5.
[0029] Example 11 Based on Example 10, the mass ratio of the composite LMFP material to Ketjen black is 155:1; S1: (1) The preparation method of the composite LMFP material is as follows: lithium carbonate, manganese carbonate, iron phosphate, dopant, and ammonium dihydrogen phosphate are added to an ethanol aqueous solution (the mass ratio of ethanol to deionized water is 1:1) and ball-milled for 7 hours, sucrose is added and ball-milled for 8 hours, and dried at 55°C to obtain a precursor; in a nitrogen atmosphere, the precursor is calcined at 500°C for 4 hours, and the temperature is raised to 700°C and calcined for 12 hours to obtain a composite LMFP material; The molar ratio of lithium carbonate, manganese carbonate, iron phosphate, dopant, diammonium phosphate and sucrose is 1:0.6:0.2:0.04:1:0.05; the molar ratio of zinc carbonate to magnesium carbonate in the dopant is 4:1; (2) The composite LMFP material, Ketjen black and Zr(SO4)2 were ball-milled at a speed of 800 rpm / min for 20 min, and sintered at 800°C for 8 hours in a nitrogen atmosphere to obtain an active material; Among them, the mass ratio of the composite LMFP material to Ketjen black is 155:1, and the mass ratio of the composite LMFP material to Zr(SO4)2 is 200:1; the sintering heating rate is 50℃ / min, and the sintering annealing rate is 25℃ / min; S2: The active material, binder (KF1100) and conductive agent (Super P) are uniformly mixed to obtain a positive electrode slurry; the positive electrode slurry is coated on a 12μm aluminum foil and dried at 120°C for 12 hours to obtain a positive electrode material; wherein the mass ratio of the active material, binder and conductive agent is 96:2.5:1.5.
[0030] Example 12 Based on Example 10, the mass ratio of the composite LMFP material to Zr(SO4)2 is 205:1; S1: (1) The preparation method of the composite LMFP material is as follows: lithium carbonate, manganese carbonate, iron phosphate, dopant, and ammonium dihydrogen phosphate are added to an ethanol aqueous solution (the mass ratio of ethanol to deionized water is 1:1) and ball-milled for 7 hours, sucrose is added and ball-milled for 8 hours, and dried at 55°C to obtain a precursor; in a nitrogen atmosphere, the precursor is calcined at 500°C for 4-5 hours, and the temperature is raised to 700°C and calcined for 12 hours to obtain a composite LMFP material; The molar ratio of lithium carbonate, manganese carbonate, iron phosphate, dopant, diammonium phosphate and sucrose is 1:0.7:0.2:0.04:1:0.05; the molar ratio of zinc carbonate to magnesium carbonate in the dopant is 4:1; and the mass ratio of ethanol to deionized water in the ethanol aqueous solution is 1:(1-2); (2) The composite LMFP material, Ketjen black and Zr(SO4)2 were ball-milled at a speed of 800 rpm / min for 20 min, and sintered at 800°C for 8 hours under a nitrogen atmosphere to obtain an active material; Among them, the mass ratio of the composite LMFP material to Ketjen black is 150:1, and the mass ratio of the LMFP material to Zr(SO4)2 is 205:1; the sintering heating rate is 50℃ / min, and the sintering annealing rate is 25℃ / min; S2: The active material, binder (KF1100) and conductive agent (Super P) are uniformly mixed to obtain a positive electrode slurry; the positive electrode slurry is coated on a 12μm aluminum foil and dried at 120°C for 12 hours to obtain a positive electrode material; wherein the mass ratio of the active material, binder and conductive agent is 96:2.5:1.5.
[0031] Comparative Example 1 is based on Example 1: In S1, Ketjen black was not introduced; S1: LMFP material and Zr(SO4)2 were ball-milled at a speed of 800 rpm / min for 20 min, and sintered at 800°C for 8 hours in a nitrogen atmosphere to obtain an active material; The mass ratio of LMFP material to Zr(SO4)2 is 205:1; the heating rate of sintering is 50℃ / min, and the annealing rate of sintering is 25℃ / min; S2: The active material, binder (KF1100) and conductive agent (Super P) are uniformly mixed to obtain a positive electrode slurry; the positive electrode slurry is coated on a 12μm aluminum foil and dried at 120°C for 12 hours to obtain a positive electrode material; wherein the mass ratio of the active material, binder and conductive agent is 96:2.5:1.5.
[0032] Comparative Example 2 is based on Example 1: In S1, Zr(SO4)2 is not introduced; S1: LMFP material, Ketjen black and Zr(SO4)2 were ball-milled at 800 rpm / min for 20 min, and sintered at 800°C for 8 h in a nitrogen atmosphere to obtain an active material; Among them, the mass ratio of LMFP material to Ketjen black is 155:1, and the mass ratio of LMFP material to Zr(SO4)2 is (200-205):1; the heating rate of sintering is 50℃ / min, and the annealing rate of sintering is 25℃ / min; S2: The active material, binder (KF1100) and conductive agent (Super P) are uniformly mixed to obtain a positive electrode slurry; the positive electrode slurry is coated on a 12μm aluminum foil and dried at 120°C for 12 hours to obtain a positive electrode material; wherein the mass ratio of the active material, binder and conductive agent is 96:2.5:1.5.
[0033] Comparative Example 3 is based on Example 1: In S1, there is no mechanical ball milling process; S1: LMFP material, Ketjen black and Zr(SO4)2 were mixed evenly, and sintered at 800°C for 8 hours in a nitrogen atmosphere to obtain an active material; Among them, the mass ratio of LMFP material to Ketjen black is 155:1, and the mass ratio of LMFP material to Zr(SO4)2 is 205:1; the heating rate of sintering is 50℃ / min, and the annealing rate of sintering is 25℃ / min; S2: The active material, binder (KF1100) and conductive agent (Super P) are uniformly mixed to obtain a positive electrode slurry; the positive electrode slurry is coated on a 12μm aluminum foil and dried at 120°C for 12 hours to obtain a positive electrode material; wherein the mass ratio of the active material, binder and conductive agent is 96:2.5:1.5.
[0034] Comparative Example 4 is based on Example 1: In S1, Ketjen black is replaced with carbon black (Super-P); S1: LMFP material, carbon black (Super-P), and Zr(SO4)2 were ball-milled at 800 rpm / min for 20 min, and sintered at 800 °C for 8 h in a nitrogen atmosphere to obtain an active material; Among them, the mass ratio of LMFP material to Ketjen black is 155:1, and the mass ratio of LMFP material to Zr(SO4)2 is 205:1; the heating rate of sintering is 50℃ / min, and the annealing rate of sintering is 25℃ / min; S2: The active material, binder (KF1100) and conductive agent (Super P) are uniformly mixed to obtain a positive electrode slurry; the positive electrode slurry is coated on a 12μm aluminum foil and dried at 120°C for 12 hours to obtain a positive electrode material; wherein the mass ratio of the active material, binder and conductive agent is 96:2.5:1.5.
[0035] Comparative Example 5 is based on Example 10, except that zinc carbonate is introduced alone; S1: (1) The preparation method of the composite LMFP material is as follows: lithium carbonate, manganese carbonate, iron phosphate, dopant, and ammonium dihydrogen phosphate are added to an ethanol aqueous solution (the mass ratio of ethanol to deionized water is 1:1) and ball-milled for 7 hours, sucrose is added and ball-milled for 8 hours, and dried at 55°C to obtain a precursor; in a nitrogen atmosphere, the precursor is calcined at 500°C for 4 hours, and the temperature is raised to 700°C and calcined for 12 hours to obtain a composite LMFP material; Wherein, the molar ratio of lithium carbonate, manganese carbonate, iron phosphate, zinc carbonate, diammonium phosphate, and sucrose is 1:0.8:0.2:0.03:1:0.05; (2) The composite LMFP material, Ketjen black and Zr(SO4)2 were ball-milled at a speed of 800 rpm / min for 20 min, and sintered at 800°C for 8 hours in a nitrogen atmosphere to obtain an active material; Among them, the mass ratio of the composite LMFP material to Ketjen black is 150:1, and the mass ratio of the LMFP material to Zr(SO4)2 is 200:1; the sintering heating rate is 50℃ / min, and the sintering annealing rate is 25℃ / min; S2: The active material, the binder (KF1100), and the conductive agent (Super P) are uniformly mixed to obtain a positive electrode slurry; the positive electrode slurry is coated on a 12 μm aluminum foil and dried at 120° C. for 12 hours to obtain a positive electrode material; Among them, the mass ratio of active material, binder and conductive agent is 96:2.5:1.5.
[0036] Testing experiment: (1) Assembly of button battery: The button battery shell uses CR2430 model, the diaphragm uses 20um diaphragm, and the electrode uses a positive electrode with uniform coating. In a glove box filled with argon, the button battery is assembled in the following order: battery shell - place positive electrode - drip electrolyte - place diaphragm - drip electrolyte - place lithium sheet - place gasket spring - battery shell.
[0037] (2) Cycle performance test: A button battery charge and discharge tester (Wuhan Blue Electric, CT3002A) was used to perform 10, 30, and 50 cycles of 0.2C charge and discharge tests on the button batteries, with a voltage range of 2.0~4.1V; the test results are shown in Table 1.
[0038] Table 1
[0039] Conclusion: In Examples 1 to 9, it can be seen from Table 1 that Example 1 is the best solution; Comparative Example 1 is based on Example 1, and S1 does not introduce Ketjen black, which leads to a decrease in the cycle performance of the battery. Comparative Example 2 is based on Example 1: S1 does not introduce Zr(SO4)2; therefore, the cycle performance of the battery is reduced, because Zr(SO4)2 provides Zr after calcination. 4+It can enhance the conductivity and stability of the electrode, and also improve the battery life. Comparative Example 3 is based on Example 1: In S1, there is no mechanical ball milling process; the ball milling process can reduce the size of LMFP, which is more conducive to its transmission during the charge and discharge process at the battery end, so the battery cycle performance of Comparative Example 3 decreases. Comparative Example 4 is based on Example 1: In S1, Ketjen black is replaced with carbon black (Super-P); resulting in a decrease in battery performance; because Ketjen black has a higher purity and a branched structure, the highly conductive Ketjen black is used to coat the LMFP material, which can not only inhibit the dissolution of manganese elements, but also greatly increase the conductivity of the material, and can improve the conductivity and cycle stability of the battery. Example 10 is based on Example 1, and zinc carbonate and yttrium carbonate are introduced into the LMFP material to improve the performance of the battery, because zinc can optimize the crystal structure, reduce the volume change caused by the insertion and deinsertion of lithium ions, and reduce the dissolution of manganese; yttrium doping can reduce LiFe x Mn y PO4 and Fe x Mn y The strain between the PO4 phase interfaces promotes the reduction kinetics of manganese ions, which is beneficial to enhancing the cycle stability of the LMFP material during the charge and discharge process. Comparative Example 5 is based on Example 10, and only zinc carbonate is introduced; therefore, the cycle stability of the battery is reduced.
[0040] Finally, it should be noted that the above is only a preferred embodiment of the present invention, but the protection scope of this application is not limited thereto. Any changes or substitutions that can be easily thought of by any technician familiar with the technical field within the spirit and principle of the present invention and within the technical scope disclosed in this application should be included in the protection scope of this application; in the absence of conflict, the embodiments of this application and the features in the embodiments can be combined with each other. Therefore, the protection scope of this application shall be based on the protection scope of the claims.
Claims
1. A method for preparing a positive electrode material for improving the cycle performance of a LMFP battery, characterized in that: The steps include: S1: LMFP material, Ketjen black and Zr(SO4)2 are mixed evenly by ball milling, and sintered in a nitrogen atmosphere to obtain an active material; S2: The active material, the binder, and the conductive agent are uniformly mixed to obtain a positive electrode slurry; the positive electrode slurry is coated on an aluminum foil, and dried to obtain a positive electrode material.
2. The method for preparing a positive electrode material for improving the cycle performance of a LMFP battery according to claim 1, characterized in that: The mass ratio of the LMFP material to Ketjen black is (150-155):1; the mass ratio of the LMFP material to Zr(SO4)2 is (200-205):
1.
3. The method for preparing a positive electrode material for improving the cycle performance of a LMFP battery according to claim 1, characterized in that: The mass ratio of the active material, the binder and the conductive agent is 96:2.5:1.5; the binder includes PVDF; and the conductive agent includes Super P.
4. The method for preparing a positive electrode material for improving the cycle performance of a LMFP battery according to claim 1, characterized in that: The process conditions of the sintering treatment are: a heating rate of 45-50°C / min, an annealing rate of 20-25°C / min, a sintering temperature of 750-800°C, and a sintering time of 7-8 hours.
5. The method for preparing a positive electrode material for improving the cycle performance of a LMFP battery according to claim 1, characterized in that: The ball milling speed is 750~800rpm / min, and the ball milling time is 18min~20min.
6. The method for preparing a positive electrode material for improving the cycle performance of a LMFP battery according to claim 1, characterized in that: The LMFP material comprises conventional LMFP material and composite LMFP material; the preparation method of the composite LMFP material comprises: adding lithium carbonate, manganese carbonate, iron phosphate, dopant and ammonium dihydrogen phosphate into an ethanol aqueous solution and ball milling and mixing for 7-9 hours, adding sucrose and continuing ball milling for 7-9 hours, and drying at 50-60° C. to obtain a precursor; in a nitrogen atmosphere, calcining the precursor at 400-500° C. for 4-5 hours, heating to 650-700° C. and calcining for 10-12 hours to obtain the composite LMFP material.
7. The method for preparing a positive electrode material for improving the cycle performance of a LMFP battery according to claim 6, characterized in that: The molar ratio of the lithium carbonate, manganese carbonate, iron phosphate, dopant, diammonium phosphate and sucrose is (1-1.2):0.8:(0.2-0.24):(0.03-0.04):1:(0.05-0.07).
8. The method for preparing a positive electrode material for improving the cycle performance of a LMFP battery according to claim 6, characterized in that: The doping agents are zinc carbonate and yttrium carbonate in a molar ratio of (4-5):1; in the ethanol aqueous solution, the mass ratio of ethanol to deionized water is 1:(1-2).
9. A positive electrode material prepared according to the method for preparing a positive electrode material for improving the cycle performance of a LMFP battery according to any one of claims 1 to 8.